Constraining labour: The integration dynamics of working‐class horticultural migrants in rural areas of Norway, the UK and the US. Issue 1 (26th January 2022) - Scott, Sam; Visser, M. Anne
Abstract: This article argues that many low‐wage migrants moving to work in rural areas of the developed world end up in very specific and precarious employment and housing contexts: working in temporary/seasonal jobs within horticultural labour markets and often living in employer‐provided tied accommodation. This context—which we profile by drawing on qualitative case study evidence from Norway, the UK and the US—makes integration virtually impossible. It is only after moving on from precarious temporary/seasonal work and out from tied accommodation that rural integration becomes viable. Yet even then, the integration of these workers is often limited. Migrants are largely 'quarantined' and separate and invisible from the host society. Not surprisingly, migrants tend to treat their lack of rural integration as 'liminal', that is, a temporary and in‐between life stage. They also engage in 'transnational simultaneity' by maintaining family/communal relations back home, whilst focusing largely on work in the host country. This liminality and transnational simultaneity help working‐class migrants survive their quarantined lives.